Daith Piercing in a Case of Chronic Migraine: A Possible Vagal Modulation - Cascio Rizzo, Angelo; Paolucci, Matteo; Altavilla, Riccardo; Brunelli, Nicoletta; Assenza, Federica; Altamura, Claudia; Vernieri, Fabrizio (Frontiers in Neurology, 2017)
Daith piercing is an ear piercing located at the crus of the helix, bilaterally. It is getting great consent on social media as alternative treatment in chronic migraine. No data about its efficacy and action are available in scientific literature so far. We present the case of a 54 year-old male patient suffering from refractory chronic migraine with medication-overuse, who substantially improved after bilateral ear daith piercing. His migraine was refractory to symptomatic as well as prophylactic therapies. He used to treat headaches with up to 5 symptomatic drugs per attack and had attempted several pharmacological preventive therapies, including Onabotulinumtoxin A. He also underwent detoxification treatments with intravenous steroids and diazepam, without durable benefit. At the time of daith piercing, the headache-related disability measures showed a HIT-6 score of 64, a MIDAS-score of 70, and a 11-point Box scale of 5. On his own free will, he decided to get a “daith piercing”. After that, he experienced a reduction of migraine attacks, which became very rare, and infrequent, less disabling episodes of tension-type headache (HIT-6 score of 56; MIDAS score of 27, 11-point Box scale of 3). Painkiller assumption has much decreased: he takes only one tablet of indomethacin 50 mg to treat tensive headaches, about 4 times per month. Beyond a placebo effect, we can speculate a vagal modulation as the action mechanism of daith piercing: a nociceptive sensory stimulus applied to trigeminal and vagal areas of the ear can activate ear vagal afferents, which can modulate pain pathways by means of projections to the caudal trigeminal nucleus, to the locus coeruleus and to the nucleus raphe magnus. Currently, daith piercing cannot be recommended as migraine treatment because of the lack of scientific evidence, the unquantified rate of failure and the associated risks with insertion. However, given the increasing but anecdotal evidence, we think that the mechanism needs testing by means of a controlled clinical trial in a population of chronic migraineurs.